2017
DOI: 10.1002/lt.24766
|View full text |Cite
|
Sign up to set email alerts
|

The release of microRNA‐122 during liver preservation is associated with early allograft dysfunction and graft survival after transplantation

Abstract: Early allograft dysfunction (EAD) after liver transplantation (LT) is associated with inferior graft survival. EAD is more prevalent in grafts from donation after circulatory death (DCD). However, accurate prediction of liver function remains difficult because of the lack of specific biomarkers. Recent experimental and clinical studies highlight the potential of hepatocyte-derived microRNAs (miRNAs) as sensitive, stable, and specific biomarkers of liver injury. The aim of this study was to determine whether mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 56 publications
(79 reference statements)
0
32
2
Order By: Relevance
“…Studies have shown that HDmiR‐122 levels in graft preservation fluid are higher in DCD grafts and in livers that went on to develop EAD and NAS . Higher HDmiR‐122 levels in perfusate were also measured in a porcine DCD NMP model with increasing warm ischemia times .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Studies have shown that HDmiR‐122 levels in graft preservation fluid are higher in DCD grafts and in livers that went on to develop EAD and NAS . Higher HDmiR‐122 levels in perfusate were also measured in a porcine DCD NMP model with increasing warm ischemia times .…”
Section: Discussionmentioning
confidence: 95%
“…In the early detection of hepatic injury during machine perfusion, miRs in perfusate offer several advantages. miRs can withstand harsh environmental conditions, and because the perfusate circulates through the entire liver during machine perfusion, miR levels in perfusate provide a better and non‐invasive representation of the entire liver compared to miR levels measured in total RNA samples from biopsies . Furthermore, miRs have been shown to be earlier and more sensitive markers of liver damage than more conventional markers such as AST or ALT, and machine perfusion potentially allows for an even more representative and dynamic evaluation of the liver graft .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, accurate prediction of liver function is still difficult due to the lack of specific biomarkers. Recent experimental and clinical studies have emphasized the potential of hepatocyte‐derived miRNAs as a sensitive, stable, and specific biomarker for liver injury . Moreover, in pancreatic islets undergoing autologous transplantation, high‐quality islets are essential for better post‐transplantation endocrine function; however, pressure during the separation affects quality and yield.…”
Section: The Potential Role Of Circulating Mirna and Circulating Dna mentioning
confidence: 99%